Achieving Smart Energy Planning Objectives. The Approach of the Transform Project - Delponte, Ilaria (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Cities play a dual role in the field of energy and integrated planning. They function as institutional planning and decision making bodies and interfere as actors, e.g. as project developers or launching customers. In the first case their attempts at integrated plans are often unsuccessful in integrating vision, goals and instruments of all stakeholders so that waste, water, energy cycles, urban planning and budgets proceed with no connection to each other. TRANSFORM Project “Transformation Agenda for Low Carbon Cities” (FP7) tries to improve the integrated energy policy and decision making process of cities, both at a strategic and operational level, by providing the cities with a framework based on overall planning experiences and on-the-field projects and qualitative and quantitative analysis support models. The project intends also to make a step further in the quality of research, by providing a replicable and tested framework for the production of a strategic Transformation Agenda for the city as a whole, combined with district Implementation Plans.